Diversity of the Family Rhacophoridae (Amphibia: Anura) in Lai Chau Province, Vietnam - Anh, Pham Van; Le Quoc Thang, Hoang; The Cuong, Pham; Quang Truong, Nguyen (VNU Journal of Science: Natural Sciences and Technology; Vol 35 No 2DO - 10.25073/2588-1140/vnunst.4880, 2019)
Abstract: This study reports on 13 species belonging to six genera of the family Rhacophoridae based on a new amphibian collection from Sin Ho district, Lai Chau province, Vietnam and the previously published tree frogs in this province. Among these, Kurixalus bisacculus, Polypedates mutus, Rhacophorus kio, and Theloderma bicolor were recorded for the first time in Lai Chau. Additional data of morphological characters and natural history of the named species are also provided. Among the 13 recorded species of Rhacophoridae from Lai Chau Province, two species are listed in the IUCN Red List (2018) and two are listed in the Red Data Book of Vietnam (2007). Keywords: New records, Sin Ho district , Kurixalus , Polypedates , Rhacophorus , Theloderma . References [1] Ủy Ban nhân tỉnh Lai Châu, Cổng thông tin điện tử. http://http://laichau.gov.vn, 2012 (cập nhật ngày 9/4/2019. [2] S.V. Nguyen, C.T. Ho, T.Q. Nguyen, Herpetofauna of Vietnam. Edition Chimaira, Frankfurt am Main, 2009. [3] R. Bourret, Les Batraciens de l’Indochine [Hanoi], Institut Océanographique de l’Indochine, 1942. [4] E.H. Taylor, The Amphibian fauna of Thailand, The University of Kansas Science Bulletin, Vol. XLIII, No.8, 1962. [5] Q. Liu, T. Wang, X. Zhai, J. Wang, Call characteristics of two sympatric and morphologically similar tree frogs species, Polypedates megacephalus and Polypedates mutus (Anura: Rhacophoridae), from Hainan, China, Asian Herpetological Research 9 (2018) 249–249. [6] IUCN, The IUCN Red List of Threatened Species. Version 2018.2.<www.iucnredlist.org>. (accessed 20 March 2019). [7] Bộ Khoa học và Công nghệ, Viện Khoa học và Công nghệ Việt Nam, Sách Đỏ Việt Nam, Phần I: Động vật. Nxb Khoa học tự nhiên và Công nghệ, Hà Nội, 2007, trang 165-217. [8] G.-h. Yu, M.-w. Zhang, J.-x. Yang, A species boundary within the Chinese Kurixalus odontotarsus species group (Anura: Rhacophoridae): New insights from molecular evidence”, Molecular Phylogenetics & Evolution 56 (2010) 942–950. [9] D.R. Frost, Amphibian Species of the World: an Online Reference. Version 6.0. Electronic Database accessible at http://research.amnh.org/ herpetology/amphibia/index.html. American Museum of Natural History, New York, USA. (accessed 20 March 2019). [10] T.D. Le, L.H.S. Nguyen, T.N. Bui, Q.T. Nguyen, First records of distribution and advertisement calls of Feihyla vitttata (Boulenger, 1887) and Polypedates magacephalus Hallowell, 1861 (Anura: Rhacophoridae) in Dien Bien Province, Vietnam, VNU Journal of Natural Sciences and Technology 30 (1S) (2014) 7-15. [11] A. Ohler, M. Delorme, Well known does not mean well studie: morphological & molecular support for existence of sibling species in the Javanese gliding frog Rhacophorus reinwardtii (Amphibia, Anura)”, Comptes Rendus, Biologies Paris 329 (2006) 86-97. [12] V.A. Pham, T.C. Pham, V.N. Hoang, T. Ziegler, Q.T. Nguyen, New records of amphibians and reptiles from Ha Giang Province, Vietnam, Herpetology Notes 10 (2017) 183-191. [13] Phạm Văn Anh, Nguyễn Quảng Trường, Các loài Ếch cây sần giống Theloderma (Amphibia: Anura: Rhacophoridae) ở tỉnh Sơn La, Tạp chí Khoa học ĐHQGHN: Khoa học Tự nhiên và Công nghệ 34(1) (2018) 48-54.